2020
DOI: 10.1200/go.20.00407
|View full text |Cite
|
Sign up to set email alerts
|

Delays Experienced by Patients With Pediatric Cancer During the Health Facility Referral Process: A Study in Northern Tanzania

Abstract: PURPOSE It is estimated that 50%-80% of patients with pediatric cancer in sub-Saharan Africa present at an advanced stage. Delays can occur at any time during the care-seeking process from symptom onset to treatment initiation. Referral delay, the time from first presentation at a health facility to oncologist evaluation, is a key component of total delay that has not been evaluated in sub-Saharan Africa. METHODS Over a 3-month period, caregivers of children diagnosed with cancer at a regional cancer center (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 39 publications
(45 reference statements)
2
16
1
Order By: Relevance
“…Inability of younger children to communicate effectively, together with vague symptoms of cancer in this age group may play a role in delay in seeking health care advice. Like many other studies, we did not find the sex of child as significant factor for patient, physician, or total diagnosis delay 1,4,14 …”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Inability of younger children to communicate effectively, together with vague symptoms of cancer in this age group may play a role in delay in seeking health care advice. Like many other studies, we did not find the sex of child as significant factor for patient, physician, or total diagnosis delay 1,4,14 …”
Section: Discussionsupporting
confidence: 70%
“…We found that higher parent's educational level was associated with shorter diagnosis delay 4,5 . Notably, many studies have consistently reported the mother’s education level as an important determinant affecting patient delay 10–12 .…”
Section: Discussionmentioning
confidence: 57%
“…[10][11][12] Patient pathways to presentation to healthcare professionals and initial management in primary care are critical determinants of outcomes in cancer. 13 Reducing diagnostic delays may improve prognosis by increasing the proportion of early-stage cancers being identified. 14 Patient delay is the period from the day the symptoms appear until the patient comes to the health facility for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…Patient pathways to presentation to healthcare professionals and initial management in primary care are critical determinants of outcomes in cancer 13 . Reducing diagnostic delays may improve prognosis by increasing the proportion of early‐stage cancers being identified 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The 63% OS of the entire stage 2 cohort appears lower than historically reported outcomes (75% OS in a prior cohort from Lilongwe, Malawi [15]; 73% OS from Mbeya, Tanzania [13]). We observed that two main factors contributed to KS‐related mortality for children with lymphadenopathic KS: [1] risk of early death in critically ill patients with delayed presentation to tertiary care, as has been described among patients with other childhood malignancies in LMIC settings [33–35], and [2] higher risk of relapse in older children categorized as stage 2. Ultimately, the majority of younger children promptly initiated on BV chemotherapy achieve long‐term CR.…”
Section: Discussionmentioning
confidence: 97%